Progesterone induces relaxation of human umbilical cord vascular smooth muscle cells through mPRα (PAQR7). (15th October 2018) - Pang, Yefei; Thomas, Peter
Abstract: Progesterone effects on vascular smooth muscle cell (VSMC) relaxation and the mechanism were investigated in cultured human umbilical vein VSMCs. Membrane progesterone receptors mPRα, mPRβ, and mPRγ were highly expressed in VSMCs, whereas nuclear progesterone receptor (nPR) had low expression. Progesterone (20 nM) and 02–0 (mPR-selective agonist), but not R5020 (nPR agonist), induced muscle relaxation in both a VSMC collagen gel disk contraction assay and an endothelium-denuded human umbilical artery ring tension assay. Progesterone and 02–0 increased ERK and Akt phosphorylation and decreased cAMP levels. These effects were blocked by preincubation with pertussis toxin. Progestin–induced muscle relaxation was blocked by pretreatment with mPRα, but not nPR, siRNAs, and by co-treatment with 8-Br-cAMP, AZD6244 (MAP kinase inhibitor), and wortmannin (PI3K inhibitor). Progestins reduced myosin light chain phosphorylation which was blocked with AZD6244 and wortmannin. These results demonstrate progesterone directly relaxes human VSMCs through mPRα/Gi and MAP kinase/ERK-, Akt/PI3K-, and cAMP-dependent pathways. Highlights: Progesterone (P4) induces human umbilical vein muscle cell relaxation through mPRα. The P4 action is nPR-independent and involves activation of an inhibitory G protein. P4-induces relaxation through activation of MAPK, Akt/PI3K and cAMP signaling. P4 treatment decreases phosphorylation of MLC resulting in muscle cell relaxation.